T lymphocyte recruitment to melanoma brain tumors depends on distinct venous vessels - Messmer, Julia M.; Thommek, Calvin; Piechutta, Manuel; Venkataramani, Varun; Wehner, Rebekka; Westphal, Dana; Schubert, Marc Cicero; Mayer, Chanté D.; Effern, Maike; Berghoff, Anna S.; Hinze, Daniel; Helfrich, Iris; et al. (Immunity, 2024)
To improve immunotherapy for brain tumors, it is important to determine the principal intracranial site of T cell recruitment from the bloodstream and their intracranial route to brain tumors. Using intravital microscopy in mouse models of intracranial melanoma, we discovered that circulating T cells preferably adhered and extravasated at a distinct type of venous blood vessel in the tumor vicinity, peritumoral venous vessels (PVVs). Other vascular structures were excluded as alternative T cell routes to intracranial melanomas. Anti-PD-1/CTLA-4 immune checkpoint inhibitors increased intracranial T cell motility, facilitating migration from PVVs to the tumor and subsequently inhibiting intracranial tumor growth. The endothelial adhesion molecule ICAM-1 was particularly expressed on PVVs, and, in samples of human brain metastases, ICAM-1 positivity of PVV-like vessels correlated with intratumoral T cell infiltration. These findings uncover a distinct mechanism by which the immune system can access and control brain tumors and potentially influence other brain pathologies.
Gesehen am 19.09.2025